A Study and Strategic Framework for Strengthening the Link and Match in Vocational Education - Fatimah, Siti; Chamidi, Agus S. (International Journal of Management, Innovation, and Education, 2024)
Developing a strong linkage between educational institutions and the labor market has become a crucial priority in building a skilled and competitive workforce. This study aims to analyze the current condition and formulate strategic frameworks to strengthen the link and match between vocational education and industry needs in Indonesia, with a specific focus on Kebumen Regency. Employing a literature review method, this research synthesizes theories, empirical findings, and policy frameworks from books, academic journals, and validated online sources. The analysis focuses on identifying the relevance and effectiveness of the Triple Helix Model a collaborative synergy between schools, industries, and local governments as a strategic approach to enhance the alignment of vocational education with employment demands. The findings reveal that the link and match policy has not yet achieved optimal results, as seen from the relatively high unemployment rates among vocational school graduates. The gap between labor supply and industrial demand persists due to curriculum mismatches, limited industrial partnerships, and insufficient local government support. The study highlights the importance of multi-stakeholder collaboration through the Triple Helix approach to design adaptive curricula, establish internship programs, provide competency certification, and ensure graduate absorption by industries. Strengthening coordination among educational institutions, industries, and local governments is essential to create sustainable, skill-based employment opportunities. This research contributes theoretically to the development of vocational education management and practically offers a strategic framework for policymakers and educational leaders to enhance the effectiveness of link and match programs toward achieving human capital competitiveness in the era of Industry 4.0.